Effects of storage duration and dilution ratio on the quality of Tre rooster sperm stored at 5 °C - Trần , Thị Thanh Khương; Nguyễn, Lâm Khánh Duy; Trần, Chí Công; Nguyễn, Huỳnh Châu Minh; Phạm, Trường Thoại Kha (Hue University Journal of Science: Natural Science, 2026)
Semen storage for artificial insemination is an important technique for maintaining and rapidly increasing livestock populations. This study was conducted to determine the optimal dilution ratio and storage duration for Tre chicken (Gallus gallus domesticus) semen stored at 5 °C. Semen samples were collected, initially evaluated for quality, then diluted with SCE extender at four different ratios (1:4, 1:6, 1:8, and 1:10) and stored for 12 hours. Sperm quality was assessed at five time points (0, 3, 6, 9, and 12 hours) based on total motility, progressive motility, viability, membrane integrity, and acrosome integrity. The results showed that the 1:6 dilution ratio maintained sperm quality comparable to the 1:4 ratio (p > 0.05) and significantly higher than the 1:8 and 1:10 ratios (p < 0.05) for most evaluated parameters. After 9 hours of storage at the 1:6 dilution ratio, total motility, progressive motility, viability, membrane integrity, and acrosome integrity reached 56.92%, 38.74%, 69.38%, 59.97%, and 75.36%, respectively. These findings indicate that storing Tre chicken semen at 5 °C with a dilution ratio of 1:6 for up to 9 hours is an effective condition in this study, with practical significance for the conservation and breeding of indigenous chicken breeds in Vietnam.